PAI Learning Media Based on Dayak Local Wisdom and Ecotheology in Health Vocational Schools - Muhammadi Fuad Ikhwansyah; Normuslim Normuslim; Hamdanah Hamdanah (LP. Ma'arif Janggan Magetan, 2025)
This study develops Islamic Religious Education (IRE) learning media based on Dayak local wisdom and eco-theology to strengthen ecological awareness at the Muhammadiyah Health Vocational School in Palangka Raya. The research employs a modified Borg & Gall R&D model through six stages, including preliminary study, planning, product development, testing, revision, and field implementation. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using qualitative and quantitative methods. Findings show the media is highly feasible, with expert validation scoring 91% for material and 88% for media design. Student responses (85%) confirmed its effectiveness in linking Islamic teachings with Dayak values—Tatadanya, Huma Betang, and Pantang Larang—in fostering environmental responsibility. Moreover, ecological awareness among students increased by 27% after implementation. The integration of Islamic eco-theology and Dayak cultural wisdom not only enhanced students’ conceptual understanding but also supported the internalization of ecological values in cognitive, affective, and psychomotor domains. This study contributes to the development of IRE media by demonstrating the value of integrating religion, local culture, and environmental education for character building and sustainability.